Study protocol for a pilot randomized controlled trial on the feasibility and preliminary efficacy of an integrated psychoeducational intervention for transition-age youths in acute psychiatric settings - Longo, Giulio; Orsolini, Laura; Premici, Alessandra; Volpe, Umberto (Frontiers in Psychiatry, 2026)
IntroductionPsychoeducation is a psychosocial intervention aimed at providing knowledge, cognitive and communication strategies to improve illness awareness and coping skills in patients with psychiatric disorders. Adolescence is a critical phase in psychopathological development. Integrating psychoeducational interventions among youngsters, since hospital clinical practice during mental illness onset, can significantly impact on the global functioning and long-term prognosis. This study aims to assess the feasibility and efficacy of a psychoeducational group intervention to reduce emotional dysregulation and affective symptomatology in a sample of youths hospitalized at the Transitional Psychiatry ward, Marche University Hospital, Ancona, Italy.MethodsParticipants (aged 15-24) will attend weekly thematic modules led by psychiatrists, psychologists and trainees. The control group will receive the treatment as usual. The modules included in the intervention will address the following topics: emotions, anxiety, psychotic experiences, addictions, sleep, therapies, communication and social skills. Participants will be assessed at baseline, at the end of the intervention and at 3-, 6- and 12 months post-randomization.ResultsWe expect to observe a significant improvement in the emotional regulation and in the secondary outcomes (mental health literacy, internalized stigma, social functioning, rehospitalization, and coping strategies). Satisfaction questionnaires will also be administered at the end of each session to identify any changes to the intervention, adapting it to patient satisfaction.ConclusionsThe protocol proposes a transdiagnostic and multimodal psychoeducational model aimed at a youth population with high clinical complexity, with potential benefits in terms of secondary prevention, therapeutic continuity and reduction of relapses. Intervention from the acute stages of the illness could ensure greater improvement in the subsequent period, while also establishing a stronger therapeutic alliance.